Prefácio e Organização - Melo, Alba Cristina M. A.; Souza, Alberto F.; Dantas, Mário Antônio R. (Anais do Simpósio em Sistemas Computacionais de Alto Desempenho (SSCAD), 2020)
Prefácio e Organização do WSCAD 2001.